Effect of Transformational Leader on Affective Commitment: The Mediating Role of Trust in Leader at Bappeda of West Sumatra Province - Resa, R.; Sandi, Hendrik Heri (Manunggal Halim Jaya, 2026)
Affective commitment is an emotional attachment of employees to an organization that plays an important role in maintaining loyalty and work effectiveness. At the Regional Development Planning Agency (Bappeda) of West Sumatra Province, low attendance rates and high absenteeism without explanation indicate weak affective commitment among employees, despite the implementation of transformational leadership. This gap highlights the need for research on the role of trust in leaders in strengthening the relationship between transformational leadership and affective commitment. This study draws on Social Exchange Theory (Blau, 1964), which states that mutually beneficial work relationships enhance trust and employee engagement. Inspiring and fair leaders encourage employee loyalty as a form of reciprocity. This study uses a quantitative approach with the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected from 74 employees of the Regional Development Planning Agency (Bappeda) of West Sumatra Province. The findings of this study conclude that: (1) Transformational leadership has a negative and insignificant effect on affective commitment, (2) transformational leadership has a positive and significant effect on trust in leaders, (3) trust in leaders has a positive and significant effect on affective commitment, (4) trust in leaders significantly mediates the influence of transformational leadership on affective commitment. This study emphasizes the importance of building trust between leaders and employees as a strategy to enhance affective commitment and organizational affectivity, particularly in the context of public organizations such as Bappeda.